2013
DOI: 10.1146/annurev-marine-121211-172337
|View full text |Cite
|
Sign up to set email alerts
|

The Oligotrophic Ocean Is Heterotrophic

Abstract: Incubation (in vitro) and incubation-free (in situ) methods, each with their own advantages and limitations, have been used to derive estimates of net community metabolism in the oligotrophic subtropical gyres of the open ocean. The hypothesis that heterotrophic communities are prevalent in most oligotrophic regions is consistent with the available evidence and supported by scaling relationships showing that heterotrophic communities prevail in areas of low gross primary production, low chlorophyll a, and warm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
163
6
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 154 publications
(177 citation statements)
references
References 83 publications
7
163
6
1
Order By: Relevance
“…Mean ± SE for (a) community respiration (CR), (b) gross primary production (GPP) and (c) net community production (NCP) (mmol O 2 m −3 d −1 ) for each season (winter, spring and summer) at the three sampled depths (surface, 20 % PAR and DCM). Duarte and Agustí, 1998;Duarte et al, 2013) and for the subtropical North Atlantic Ocean (Duarte et al, 2001;González et al, 2002;Serret et al, 2002Serret et al, , 2006Morán et al, 2004;Aranguren-Gassis et al, 2011). However, some studies have also shown balanced metabolism (Williams, 1998;Aranguren-Gassis and Serret, 2012) or a prevalence of autotrophic communities (Kähler et al, 2010), leading to challenges in the view that oligotrophic regions of the ocean support heterotrophic plankton communities (Williams et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Mean ± SE for (a) community respiration (CR), (b) gross primary production (GPP) and (c) net community production (NCP) (mmol O 2 m −3 d −1 ) for each season (winter, spring and summer) at the three sampled depths (surface, 20 % PAR and DCM). Duarte and Agustí, 1998;Duarte et al, 2013) and for the subtropical North Atlantic Ocean (Duarte et al, 2001;González et al, 2002;Serret et al, 2002Serret et al, , 2006Morán et al, 2004;Aranguren-Gassis et al, 2011). However, some studies have also shown balanced metabolism (Williams, 1998;Aranguren-Gassis and Serret, 2012) or a prevalence of autotrophic communities (Kähler et al, 2010), leading to challenges in the view that oligotrophic regions of the ocean support heterotrophic plankton communities (Williams et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…6.4 in Ciais et al, 2013). Moreover, the carbon exported to the open ocean contributes to subsidizing heterotrophic metabolism in open ocean communities, contributing to supporting the excess community respiration over production often encountered in the oligotrophic ocean (Duarte et al, 2013b;Barrón and Duarte, 2015).…”
Section: The Fate Of the Production Of Vegetated Coastal Habitatsmentioning
confidence: 99%
“…While interpretation of results is challenging and controversial (Williams et al, 2013;Duarte et al, 2013), the direct measurement of CO 2 in the ocean is difficult (Riser and Johnson, 2008). However, as O 2 and C are linked by a stoichiometric ratio (Anderson and Sarmiento, 1994), using in situ measurements of O 2 can offer several advantages over measuring CO 2 directly: dissolved O 2 is chemically neutral, while CO 2 reacts with water to form carbonic acid, which further reacts with other compounds such as carbonates.…”
Section: Introductionmentioning
confidence: 99%
“…Estimating net community production rates in the ocean is notoriously difficult (Williams et al, 2013;Duarte et al, 2013). This is in part because the net state is finely balanced between large opposing fluxes and measurements have large uncertainties (Ducklow and Doney, 2013).…”
Section: Introductionmentioning
confidence: 99%